(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-19-25 This article provides a historical perspective on the famous Chekhovian story that has been previously viewed only as a story of love with the main focus on characters’ psychology. The new approach refers to a historical climate in Russian in the end of 19 century when religion lost its primary value. The conflict between the main characters is interpreted as a conflict between religious and secular mentality. Chekhov talks about a tendency of changing values in society, when the natural man’s mentality dominates the sacramental sphere, declares its morality false, ridiculous and even harmful. Gurov cannot understand Anna Sergeevna’s repentance, because he gravitates towards the progressive pole. The institution of marriage is not sacred for him, and, like for many of his contemporaries, a church wedding ceremony is no more than just a beautiful ritual. Just as another Chekhovian character, Voinitsky, Gurov doesn’t consider cheating on a spouse a great sin. He is a man of modern tendencies. For him, God is an abstract, mythical, speculative, philosophical concept not applicable to his own life that he lives in accordance with the tendencies of a secular society. Critics often associate the image of the dog with Anna Sergeevna, but in reality it is connected rather to Gurov. First of all, the sex of the dog is male, not female (Spitz is a male). Also, in the story, the dog loves his owner, Anna Sergeevna, but he could never understand the reason for her sadness. In the same way, Gurov, though being in love with Anna Sergeevna, would never understand fully what makes her so upset. Keywords: Chekhov, “The Lady with the dog”, faith, sin, freedom/ unfreedom, Spitz.